2014
DOI: 10.1038/ncomms6022
|View full text |Cite
|
Sign up to set email alerts
|

Topological transport and atomic tunnelling–clustering dynamics for aged Cu-doped Bi2Te3 crystals

Abstract: Enhancing the transport contribution of surface states in topological insulators is vital if they are to be incorporated into practical devices. Such efforts have been limited by the defect behaviour of Bi2Te3 (Se3) topological materials, where the subtle bulk carrier from intrinsic defects is dominant over the surface electrons. Compensating such defect carriers is unexpectedly achieved in (Cu0.1Bi0.9)2Te3.06 crystals. Here we report the suppression of the bulk conductance of the material by four orders of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
16

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 55 publications
3
58
0
16
Order By: Relevance
“…Sample Preparation : As in our previous report, the (Sm x Bi 1– x ) 2 Se 3 samples with x = 0, 0.002, 0.005, 0.025, and 0.05 were prepared by the melting method, during which mixed high‐purity Bi, Se, and Sm powders (99.999% purity, Alfa Aesar, in a designed molar ratio) were sealed in clean silica ampoules. The mixtures were then heated to 950 °C throughout one day and kept at this temperature for five days, while being slowly stirred at a speed of 5 turns/minute.…”
Section: Methodsmentioning
confidence: 99%
“…Sample Preparation : As in our previous report, the (Sm x Bi 1– x ) 2 Se 3 samples with x = 0, 0.002, 0.005, 0.025, and 0.05 were prepared by the melting method, during which mixed high‐purity Bi, Se, and Sm powders (99.999% purity, Alfa Aesar, in a designed molar ratio) were sealed in clean silica ampoules. The mixtures were then heated to 950 °C throughout one day and kept at this temperature for five days, while being slowly stirred at a speed of 5 turns/minute.…”
Section: Methodsmentioning
confidence: 99%
“…In this system, B atoms act as 0-D defects, i.e., dopants, to contribute charge carriers; grain boundaries act as 2-D defects; and Si grains are 3-D defects. The synergy of defects with different dimensionality greatly enhances the TE performance: charge carriers that donated from dopants flow irreversibly into the host matrix, the mobility is largely retained because the host matrix contains fewer point defects, Electron microscope images of defects observed in Bi2Te3: (e) 0-D Cu dopants [9], (f) 1-D dislocations [10], (g) 2-D grain boundaries [11], (h) 3-D NiTe nanoinclusions [12]. and the final electrical conductivity could be higher than the conductivity of both of the components separately.…”
Section: Cross-dimensional Defect Engineeringmentioning
confidence: 98%
“…In 2011, Liu et al [10] proposed the presence of Cu ions in the van der Waals gap of Bi 2 Te 2.7 Se 0.3 via the characterization and analysis of electrical transport properties and lattice parameters. In 2014, theoretical calculations showed that the formation energy of Cu intercalation in p-type Bi 2 Te 3 is favorable [11]. Another point is that the Cu atoms prefer to enter the Sb sites due to the small electronegativity and radius difference between Cu and Sb [12,13].…”
Section: Introductionmentioning
confidence: 99%